Case Report: short stature, kidney anomalies, and cerebral aneurysms in a novel homozygous mutation in the PCNT gene associated with microcephalic osteodysplastic primordial dwarfism type II - Petraroli, Maddalena; Percesepe, Antonio; Piane, Maria; Ormitti, Francesca; Castellone, Eleonora; Gnocchi, Margherita; Messina, Giulia; Bernardi, Luca; Patianna, Viviana Dora; Esposito, Susanna Maria Roberta; Street, Maria Elisabeth (Frontiers in Endocrinology, 2023)
We report the case of a boy (aged 3 years and 7 months) with severe growth failure (length: -9.53 SDS; weight: -9.36 SDS), microcephaly, intellectual disability, distinctive craniofacial features, multiple skeletal anomalies, micropenis, cryptorchidism, generalized hypotonia, and tendon retraction. Abdominal US showed bilateral increased echogenicity of the kidneys, with poor corticomedullary differentiation, and a slightly enlarged liver with diffuse irregular echotexture. Initial MRI of the brain, performed at presentation, showed areas of gliosis with encephalomalacia and diffused hypo/delayed myelination, and a thinned appearance of the middle and anterior cerebral arteries. Genetic analysis evidenced a novel homozygous pathogenic variant of the pericentrin (PCNT) gene. PCNT is a structural protein expressed in the centrosome that plays a role in anchoring of protein complexes, regulation of the mitotic cycle, and cell proliferation. Loss-of-function variants of this gene are responsible for microcephalic osteodysplastic primordial dwarfism type II (MOPDII), a rare inherited autosomal recessive disorder. The boy died at 8 years of age as a result of an intracranial hemorrhage due to a cerebral aneurism associated with the Moyamoya malformation. In confirmation of previously published results, intracranial anomalies and kidney findings were evidenced very early in life. For this reason, we suggest including MRI of the brain with angiography as soon as possible after diagnosis in follow-up of MODPII, in order to identify and prevent complications related to vascular anomalies and multiorgan failure.